The Protective Effect of Lidocaine on Septic Rats via the Inhibition of High Mobility Group Box 1 Expression and NF-κB Activation - Huan-Liang Wang; Yan-Qiu Xing; Ying-Xue Xu; Fei Rong; Wei-Fu Lei; Wen-Hua Zhang (Mediators of Inflammation)
Lidocaine, a common local anesthetic drug, has anti-inflammatory effects. It has demonstrated a protective effect in mice from septic peritonitis. However, it is unknown whether lidocaine has effects on high mobility group box 1 (HMGB1), a key mediator of inflammation. In this study, we investigated the effect of lidocaine treatment on serum HMGB1 level and HMGB1 expression in liver, lungs, kidneys, and ileum in septic rats induced by cecal ligation and puncture (CLP). We found that acute organ injury induced by CLP was mitigated by lidocaine treatment and organ function was significantly improved. The data also demonstrated that lidocaine treatment raised the survival of septic rats. Furthermore, lidocaine suppressed the level of serum HMGB1, the expression of HMGB1, and the activation of NF-κB p65 in liver, kidneys, lungs, and ileum. Taken together, these results suggest that lidocaine treatment exerts its protective effection on CLP-induced septic rats. The mechanism was relative to the inhibitory effect of lidocaine on the mRNA expression level of HMGB1 in multiple organs, release of HMGB1 to plasma, and activation of NF-κB.